2017
DOI: 10.4103/0971-9261.194613
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status of patients of congenital pouch colon following definitive surgery

Abstract: Purpose:To assess the nutritional status in 31 patients of congenital pouch colon (CPC) who had undergone definitive surgery and closure of a protective stoma, if any, at least 1 year earlier and were below 14 years age.Materials and Methods:The clinical history, demographic details, anthropometric measurements, and results of hematological and biochemical tests were recorded. In addition to collective data, analysis was also performed after grouping by age, subtype of CPC (Types I/II and Types III/IV CPC), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…[47] A more recent study from our center of 31 patients, at least 3 years old, showed severe fecal incontinence with continence score[52] of 5 or less in 20 patients (64.52%). [48] The remaining 11 patients (25.81%), including the 10 patients with Types III/IV CPC, had “poor” fecal continence. [52] There was a high incidence of malnutrition, especially “stunting” (low height-for-age) which was the most common in the 0–5 years age-group.…”
Section: Results Of Treatment and Long-term Follow-upmentioning
confidence: 99%
See 4 more Smart Citations
“…[47] A more recent study from our center of 31 patients, at least 3 years old, showed severe fecal incontinence with continence score[52] of 5 or less in 20 patients (64.52%). [48] The remaining 11 patients (25.81%), including the 10 patients with Types III/IV CPC, had “poor” fecal continence. [52] There was a high incidence of malnutrition, especially “stunting” (low height-for-age) which was the most common in the 0–5 years age-group.…”
Section: Results Of Treatment and Long-term Follow-upmentioning
confidence: 99%
“…[52] There was a high incidence of malnutrition, especially “stunting” (low height-for-age) which was the most common in the 0–5 years age-group. [48] Patients with Types I/II CPC had a higher incidence of anemia and severe fecal incontinence than those with Types III/IV CPC. Patients with Types I/II CPC, managed by excision of the colonic pouch had a higher incidence of severe fecal incontinence and malnutrition than those with pull-through after TC, suggesting that the latter procedure has long-term benefit.…”
Section: Results Of Treatment and Long-term Follow-upmentioning
confidence: 99%
See 3 more Smart Citations